Pulsed microwave pretreatment of fresh microalgae for enhanced lipid extraction. (1st June 2022) - Zhang, Yi; Soldatov, Sergey; Papachristou, Ioannis; Nazarova, Natalja; Link, Guido; Frey, Wolfgang; Silve, Aude
Abstract: Pulsed microwave (PMW) is considered as an energy-saving pretreatment for microalgae. The efficiency of PMW was studied using a generator delivering square-pulsed modulated microwave in continuous flow on fresh Auxenochlorella protothecoides suspension. The efficiency was evaluated by measuring the increase of the suspension's conductivity, the liberation of carbohydrates, the percentage of permeabilized microalgae cells and the lipid yield after solvent extraction. The properties of the pulses i.e. pulse duration, repetition rate and pulse power had little effect on the efficiency and especially on lipid extraction performance. Lipid yield was positively correlated with the energy input and increased from 3.81% to 38.42% with microwave energy input increasing from 1.4 to 2.8 MJ/kgDW (Dry Weight). At a given PMW absorbed energy, the lipid yield decreased with the increase of algal concentration, whereas it increased with the suspension flow rate. Based on comparison with water-bath heating i.e. a pure thermal treatment, results suggest that both the microwave induced heating and non-thermal effects impact the efficiency of PMW treatment. An energy consumption of 2.53 MJ/kgDW achieved 37.29% lipid yield, which confirms that PMW is a potentially competitive, highly efficient and easy to implement method that could benefit downstream processing of microalgae.